Agronomic Values of Anaerobically Digested Cattle Manure and the Separated Solids for Barley Forage Production. Issue 6 (1st December 2016) - Hao, Xiying; Thomas, Ben W.; Nelson, Virginia; Li, Xiaomei
Abstract : Core Ideas: Agronomic values of anaerobically digested solid cattle manure are poorly defined. Separated solids of anaerobically digested cattle manure supplied N similar to cattle manure. Anaerobically digested cattle manure had high NH4 –N/total N ratio. Anaerobically digested cattle manure had less P buildup than cattle manure. Digestate separated solids can be managed similar to cattle manure. As biogas production expands, digestates from that industry are increasingly available as potential nutrient sources for crop production, but their agronomic value is poorly understood. Thus, a 5‐yr field experiment was conducted to determine the agronomic values of anaerobically digested solid beef cattle feedlot manure (ADM) and the separated solids (SS) from ADM under a semiarid reduced‐tillage dryland barley ( Hordeum vulgare L.) forage cropping system. Three organic amendments, ADM, SS, and undigested solid beef cattle feedlot manure (CM), were applied annually at 200 or 400 kg total N ha −1 for 4 yr, while the residual effect was examined in the fifth year. The higher N and P availability in ADM translated into greater barley forage yields, total N uptake, amendment‐derived N uptake, and apparent N recovery (ANR) from ADM‐amended soil than SS‐ and CM‐amended soils, while there were no significant differences between soils receiving SS or CM. The ANR was 22% for ADM but only 12% for CM and 9% for SS. In contrast, P uptake, the fraction of amendment‐derived P uptake, and apparent P recovery were similar among all amendments. Similar yields, ANR, post‐harvest soil NH4, NO3, and Olsen‐P concentrations between SS‐ and CM‐amended soils suggest that they have a comparable agronomic value. Less residual Olsen‐P in soil receiving ADM than SS or CM suggests that ADM is a lower risk for P accumulation when applied at N‐based rates. We recommend that current agronomic values for cattle feedlot manure could be applied to SS but not ADM.